2016
DOI: 10.1016/j.neulet.2016.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Nestin-positive/SOX2−negative cells mediate adult neurogenesis of nigral dopaminergic neurons in mice

Abstract: The primary clinical motor symptoms of Parkinson’s disease (PD) result from loss of dopaminergic (DA) neurons in the substantia nigra (SN). Consequently, neurogenesis of this group of neurons in the adult brain has drawn considerable interest for the purpose of harnessing endogenous neurogenerative potential as well as devising better strategies for stem cell therapy for PD. However, the existence of adult neurogenesis for DA neurons within the SN remains controversial. To overcome technical and design limitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…6 months after the start of a 6 week treatment with tamoxifen, mice with Nestin -mediated tyrosine hydroxylase deletion showed lower numbers of tyrosine hydroxylase + neurons in substantia nigra, while no reduction was observed following Sox-2 -mediated excision. This finding further supports that Nestin-expressing cells regenerate dopaminergic neurons [ 101 ]. Previously discussed factors related to limitations of in vivo models may have influenced these controversial results that deserve further investigation and are highly relevant in search for therapeutic targets in Parkinson’s disease.…”
Section: Role Of Nestin + Cells In Pathogenesis Ansupporting
confidence: 83%
“…6 months after the start of a 6 week treatment with tamoxifen, mice with Nestin -mediated tyrosine hydroxylase deletion showed lower numbers of tyrosine hydroxylase + neurons in substantia nigra, while no reduction was observed following Sox-2 -mediated excision. This finding further supports that Nestin-expressing cells regenerate dopaminergic neurons [ 101 ]. Previously discussed factors related to limitations of in vivo models may have influenced these controversial results that deserve further investigation and are highly relevant in search for therapeutic targets in Parkinson’s disease.…”
Section: Role Of Nestin + Cells In Pathogenesis Ansupporting
confidence: 83%
“…Various endogenous factors have also been implicated in the modulation of SN neurogenesis. For example, Albright et al ( 2016 ) found that a population of nestin-positive cells contributes to dopaminergic neuron turnover in this brain structure (Albright et al, 2016 ). Furthermore, using a 6-OHDA mouse model, Padel et al ( 2016 ) also showed that platelet-derived growth factor (PDGF) can lead to the restoration of nigrostriatal fiber tracts (Padel et al, 2016 ).…”
Section: “Novel” Adult Neurogenic Zonesmentioning
confidence: 99%
“…In contrast to studies on mammals, the results on juvenile chum salmon showed the presence of Nes+ cells not only in the matrix zones, but also outside them; in particular, in the parenchymal layers of the tegmentum, where the concentration of such elements was significantly higher than the number of Nes+ cells in the PVZ. Thus, the PZ of juvenile chum salmon should be considered in terms of the neurogenic potential comparable to that in PVZ, taking into account the fact that nestin is not expressed by mature neurons [40], being replaced by neuron-specific and glio-specific proteins in mature cells [41].…”
Section: Investigation Of Neuronal Progenitor Cells In the Tegmentum mentioning
confidence: 99%